Microbiological analysis of ready to eat foods collected from different places of Dhaka city, Bangladesh - Uddin, Md Aftab (Stamford Journal of Microbiology, 2019)
The current study was attempted to observe the microbiological quality of ready to eat foods collected from different places of Dhaka city, Bangladesh. Ten food samples that include five fried items-fried chicken, fish fillet, shrimp fries, French fries, potato chop and five sweet items-yoghurt, pudding, ice cream, mango drink, lemon drink were analyzed during the period from September 2017 to November 2017. Conventional cultural, microscopic and biochemical tests were followed for the detection and enumeration of bacterial isolates associated with these food samples. The investigation encompassed detection of total viable bacterial count (TVBC) and presumptive identification of other pathogenic bacteria from these samples. The higher counts of TVBC, Escherichia coli, Staphylococcus aureus and Bacillus spp. were recorded as 1.94×106 cfu/g (potato chop), 3.1×104 cfu/g (fried shrimp), 7.5×103 cfu/g (fried chicken) and 1.0 x 103 cfu/g (French fries) respectively. Based on the specifications by International Commission for Microbiological Specification for Foods (ICMSF), the level of contaminations was within acceptable microbiological limits except for potato chop. Stamford Journal of Microbiology, Vol.8(1) 2018: 30-33